Determinants of lending behaviour : evidence from Malaysian commercial banks / Rafizatul Nabila Abdul Razak - Abdul Razak, Rafizatul Nabila (2019)
This study examines the determinants of lending behaviour for commercial banks in Malaysia. Total loans and advances scaled by total assets is used as a proxy for bank lending behaviour. Six (6) independent variables that consist of three (3) internal factors and three (3) external factors were used this study. The internal factors include size, deposits, and liquidity, while the external factors are inflation, Gross Domestic Product and lending rate. Out of six (6) independent variables, only four (4) independent variables, which are liquidity, deposits, inflation, and Gross Domestic Product were included in the final model. These variables were chosen using the Stata command, vselect, which was developed by Lindsey and Sheather (2010). The target population for of this study was financial institutions in Malaysia. The final sample includes 23 Malaysian commercial bank for the period of 2012 to 2017. The data was collected from banks’ annual financial statements which were downloaded from the banks’ official website and World Development Indicators by World Bank. This study used static model of panel data, where panel specification tests and diagnostic tests were done to see the relationship of different variables with bank lending behaviour. The results of the analysis revealed that out of the four (4) factors, liquidity, inflation, and Gross Domestic Product appeared to be significantly associated with bank lending behaviour. Inflation are positively related to bank lending behaviour, whereas liquidity and gross domestic product are negatively related to the bank lending behaviour. Volume of deposits do not appear to be significantly related to bank lending behaviour.